Perkembangan Permukiman dan Pengaruhnya Terhadap Daya Dukung Lahan Kota Salatiga - Rahmawan, Salis; Juhadi, Juhadi; Santoso, Apik Budi (Geo-Image, 2019)
This study aimed to find out how much the development of settlements and their effects on the carrying capacity of land in Salatiga City. Data collection techniques used documentation and observation. The analysis technique used quantitative descriptive analysis methods. The method for calculating the carrying capacity of land used the formula for carrying capacity of residential land. The results of interpretation of satellite imagery using the Quickbird imagery in 2006 and 2016 indicated that settlement developments occured in almost every urban village except Kalicacing and Gendongan Urban Villages. The highest development of settlements occurred in the Dukuh Urban Village which is equal to 15.93 Ha and the highest percentage of development occurred in Tegalrejo Urban Village, which was 6.26%. The results of the carrying capacity calculation shiwed that the level of carrying capacity of residential land on average has decreased and the village which has decreased carrying capacity of <1 in 2016 is Tegalrejo Urban Village, which means that the area could not accommodate residents to settle. Population pressure and settlement development affect value of land carrying capacity.